Butyrylcholinesterase-knockout reduces brain deposition of fibrillar β-amyloid in an Alzheimer mouse model. (9th July 2015) - Reid, G. Andrew; Darvesh, Sultan
Abstract : Graphical abstract: Highlights: The 5XFAD mouse model of AD has butyrylcholinesterase associated with many brain Aβ plaques. Female 5XFAD mice show greater accumulation of plaque pathology, stained for Aβ or butyrylcholinesterase, than male mice. The absence of BChE results in diminished fibrillar Aβ, especially in male mice. Abstract: In Alzheimer's disease (AD), numerous β-amyloid (Aβ) plaques are associated with butyrylcholinesterase (BChE) activity, the significance of which is unclear. A mouse model, containing five human familial AD genes (5XFAD), also develops Aβ plaques with BChE activity. Knock-out of BChE in this model showed diminished fibrillar Aβ plaque deposition, more so in males than females. This suggests that lack of BChE reduces deposition of fibrillar Aβ in AD and this effect may be influenced by sex.